Water Quality Index of Euphrates River Near Al- Musayyab Power Plant - Makki, Ikhlas M.; Manii, Jwad K. (Iraqi Journal of Science, 2020)
This research deals with analyzing samples of water from the Euphrates River before and after (50m, 200m, 500m, and 1000m from the outflow)the power plant of AL-Musayyab. A Water Quality Index (WQI) analysis was performed, which is a helpful tool for rapid estimation of the quality of any water resource.. Water quality of the river was classified into good, poor, very poor, and unsuitable for drinking, based on physico-chemical parameters such as pH, total hardness (TH), and concentrations of the major ions of calcium (Ca+2), sodium (Na+), magnesium (Mg+2), potassium (K+), nitrate (NO3-2), sulphate (SO4-2), phosphate (PO4-2), and Chloride (Cl-), which indicate the extent of pollution. The study shows the deterioration of water quality, with the main candidate causes of being the direct discharge of the power plant into the river and high anthropogenic activities.